Choreography observed - Anderson, Jack, 1935- (University of Iowa Press, 1997)
For over twenty years Jack Anderson has been writing about dance performances. His essays and reviews have appeared in daily newspapers, specialist monthlies, and critical quarterlies. For the last ten years he has been a dance critic for the New York Times. In Choreography Observed, Jack Anderson has selected writings that focus most directly on choreographers and choreography in order to illuminate the delights and problems of dance and to reveal the nature of this nonverbal but intensely expressive art form. His essays and reviews deal with individual choreographers from Bournonville, Petipa.